Structural models of effective factors for build operate transfer power plant projects in Iran - Bahman Salami, 1972-, author 558374; Aminah Md. Yusof 559506; Fakulti Kejuruteraan Awam 8022 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Thesis (Doktor Falsafah (Kejuruteraan Awam - Pengurusan Pembinaan))